Impact of a Comprehensive Financial Resource on Financial Toxicity in a National, Multiethnic Sample of Adult, Adolescent/Young Adult, and Pediatric Patients With Cancer. Issue 2 (15th February 2023) - Ragavan, Meera V.; Mora, Rosa V.; Winder, Kate; Incudine, Andrea; Cunningham, Rosie; Stivers, Tom; Borno, Hala T.
Abstract : PURPOSE: Financial toxicity is a well-recognized problem for patients with cancer. However, a crucial gap remains in describing and implementing mitigation strategies. We conducted a national survey of a multiethnic adolescent/pediatric and adult patient population served by Family Reach, a nonprofit organization focused on removing financial barriers to cancer care, to evaluate the impact of a comprehensive financial resource on patient-reported financial toxicity. METHODS: An electronic survey was administered to characterize patients' current financial health and the impact of Family Reach's resources on financial toxicity. The survey was e-mailed to all patients or caregivers who received resources from Family Reach between January 1, 2020, and June 30, 2020. Factors associated with higher financial stress and higher potential impact of resources on financial burden were evaluated through separate multivariate regression models. Qualitative responses were analyzed using manual coding and thematic analysis. RESULTS: Three hundred thirty socioeconomically and racially diverse respondents (overall response rate 40%; 46% non-Hispanic White; 48% with incomes below the federal poverty line) completed the survey and were included in the analysis. More than half of respondents reported high financial stress in the previous week. Hispanic ethnicity, Black race, and low annual household income were associated with higher financial toxicity. A greater amount of financial assistance was associated with a higher confidence rating that resources provided would decrease financial stress. In open-ended comments, respondents highlighted the impact of the COVID-19 pandemic and resulting job loss on financial toxicity, the importance of financial navigation, the benefits of financial assistance, and anxiety about long-term financial health. CONCLUSION: A comprehensive financial resource, particularly financial assistance, alleviated financial toxicity in a multiethnic national sample of patients with cancer. Ongoing work is critical to address sustainable funding sources and financial navigation to support patients during treatment and survivorship.